Penguatan Produk Jamu Herbal Sebagai Daya Tarik Desa Ekowisata Pampang Gunungkidul Yogyakarta - Kartika Fajar Nieamah; Wahyuni Fajar Arum; Nanik Rianadita Sari (STIE Pariwisata API Yogyakarta, 2019)
Pampang Ecotourism Village is one of the Ecotourism villages located in Gunungkidul. This ecotourism village was established in 2017 with 1,440 tourists. Many packages are offered in this ecotourism village, one of which is herbal medicine. In the development of Pampang Ecotourism Village, there are many obstacles faced by management, including the development of herbal medicine. This community service activity aims to assist in strengthening herbal medicinal products as one of Pampang's tourist attractions. The steps that will be taken in overcoming the problems of managers are divided into three fields, namely marketing, tourism, and the handicraft industry. The results of this community service activity have been held counseling about strengthening herbal products, where residents can sell several types of herbal medicine to increase the attraction in Pampang. In addition, providing counseling to residents to cultivate herbal plants in order to add types and quantities of herbal plants. Provide counseling on herbal tour packages in making tourist brochures.